Berinvestasi di Saham-saham Thirdliner. Apa saja Rasio Fundamental yang Menentukan? - Robith Hudaya (Sekolah Tinggi Ilmu Ekonomi AMM, 2020)
This study aims to see which fundamental ratios affect investment in thirdliner companies for the observation period of 1 year investment and 3 years investment. There are four fundamental ratios: price earning ratio (PER), price to book value (PBV), return on assets (ROA), and net profit margin (NPM) used to determine the growth of the company's stock price in the first year after purchase and the third year after purchase. Using sample thirdliner companies on the Indonesian Stock Exchange from 2014 to 2019, it was found that return on assets (ROA) had a significant negative effect on the company's stock price growth for 1 year of investment. Whereas for the investment period of 3 years, it was found that the price to book value (PBV) had a significant negative effect on the company's stock price growth